LOCAL WISDOM VALUES OF JAVANESE CHILDREN’S TRADITIONAL GAMES: A METHAPHORICAL ECOLINGUISTIC VIEW - Rahardi, Kunjana; Setyaningsih, Yuliana (Masyarakat Linguistik Indonesia, 2019)
This research focuses on the description of local wisdom values in the traditional children’s games based on the local Javanese culture. The locational research data source was the Javanese children living in a Javanese community, especially those in Yogyakarta. The substantive data was the local wisdom values contained in the traditional children’s games. The data was gathered by using the observation method, namely by observing texts of traditional children’s games available during the research timeline. The techniquesused to apply theobservation method wererecording and note-taking. Besides the observation method, interviewing methods were also applied. Interview was conducted to several experts who understand the local wisdom values contained in the Javanese traditional children’s games. In addition, the interview was conducted to children who play the traditional children’s games. Data analysis was carried out using distributional and content analysis methods. This research applies the methaphorical ecolinguistic view –which involves social,cultural, and ethnic perspectives–toanalyze the data. The local wisdom values found in this research are(1) solidarity,(2)balance,(3) synergy,(4) sportsmanship,(5) agility and resilience,(6) agility and precision, and(7) obedience to norms.